1996
DOI: 10.1117/12.239053
|View full text |Cite
|
Sign up to set email alerts
|

<title>Pseudoelastic theory of shape memory alloys</title>

Abstract: This paper presents an extension of the authors' previous analyses on the one-dimensional pseudoelastic theory of shape memory alloys (SMA), in which an interaction energy has been introduced to represent the energy dissipation during the phase transformation. From the equilibrium condition of the two-phase state, we show that the partial derivative of the interaction energy with respect to the phase fraction represents the thermodynamic driving force for the phase transformation. Two functions for the interac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

1997
1997
2008
2008

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 5 publications
0
13
0
Order By: Relevance
“…Matsuzaki (1996 and1997a) have concluded that no transformations may proceed in the stress range between a and cr and z is kept constant during the process of unloading and reloading. The stress-strain relationship and the …”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…Matsuzaki (1996 and1997a) have concluded that no transformations may proceed in the stress range between a and cr and z is kept constant during the process of unloading and reloading. The stress-strain relationship and the …”
Section: Discussionmentioning
confidence: 98%
“…In other words, the partial derivative of the interaction energy with respect to the fraction of the martensite, døaM/dZ, represents the TDF during the martensitic transformation. As for the TDF, there exists a positive value, AGOM, at which both the austenitic and the martensitic phase are stable and the phase transformation proceeds along the two-phase equilibrium state Matsuzaki, 1996, and1997a), that is, (*PaM g1 -g2 + ce0 = i\GOM for the martensitic transformation. (13) Similarly, the TDF of the reverse transformation is given by a positive value of AGOA: (1) and (1 1), we obtain (e 2) = 01 -02 (*Pa…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In order to make use of the hysteresis of these SMA films or wires, it is important to understand these characteristics of SMAs and to predict their thermomechanical behavior accurately. Therefore, Matsuzaki and co-workers [2][3][4][5][6][7][8][9] have performed analytical studies on SMA's thermomechanical characteristics. Some numerical results will also briefly be described.…”
Section: Passive Damping Enhancement Using Smasmentioning
confidence: 99%